1978
DOI: 10.1530/acta.0.0870055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Depletion of Brain Noradrenaline on the Plasma FSH and Growth Hormone Levels in Ovariectomized Rats

Abstract: The electrolytic lesion of locus coeruleus reduced the hypothalamic noradrenaline (NE) content to 28 % of the control values and resulted in a marked decrease of the plasma FSH level in ovariectomized rats before puberty. The local microinjection of 6-OH-dopamine into the locus coeruleus led to a reduction in the hypothalamic NE content to 21 % of the control level and induced a decrease of the compensatory ovarian hypertrophy and that of the plasma FSH level. The electrolytic lesion of the locus coeruleus or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Conversely, several pieces of evidence suggest that LC may directly participate to gonadotropin secretion and thus its impairment might significantly affect the ovarian cycle. Endroczi and colleagues found that follicle-stimulating hormone plasma levels were reduced after LC lesion (Endroczi et al 1978 ); furthermore, LC lesion affects luteinizing hormone secretion both in basal conditions and during ovulation (Dotti and Taleisnik 1982 , 1984 ; Franci and Antunes-Rodrigues 1985 ; Anselmo-Franci et al 1997 ; Martins-Afférri et al 2003 ).…”
Section: Connections Between the Lc And The Hypothalamus: Potential Functional Effects Of Lc Lossmentioning
confidence: 99%
“…Conversely, several pieces of evidence suggest that LC may directly participate to gonadotropin secretion and thus its impairment might significantly affect the ovarian cycle. Endroczi and colleagues found that follicle-stimulating hormone plasma levels were reduced after LC lesion (Endroczi et al 1978 ); furthermore, LC lesion affects luteinizing hormone secretion both in basal conditions and during ovulation (Dotti and Taleisnik 1982 , 1984 ; Franci and Antunes-Rodrigues 1985 ; Anselmo-Franci et al 1997 ; Martins-Afférri et al 2003 ).…”
Section: Connections Between the Lc And The Hypothalamus: Potential Functional Effects Of Lc Lossmentioning
confidence: 99%
“…In Alzheimer Type Dementia (ATD), both the concentration of noradrenaline and the noradrenaline transporters sites are significantly decreased in a number of brain regions including the Locus coeruleus, cingulate gyrus, putamen, hypothalamus, medial thalamic nucleus, and raphe area (Arai et al, 1984;Tejani et al, 1993). Evidence has accumulated suggesting that noradrenaline is also involved in controlling body temperature (Lin et al, 1981, Sallinen et al, 1997, endocrine secretion (Endroczi et al, 1978;Valet et al, 1989;Ruffolo et al, 1991), and sexual behaviour (Morales et al, 1987;Guiliano & Rampin, 1997).…”
Section: Noradrenaline Functionsmentioning
confidence: 99%
“…In Alzheimer Type Dementia (ATD), both the concentration of noradrenaline and the noradrenaline transporters sites are significantly decreased in a number of brain regions including the Locus coeruleus, cingulate gyrus, putamen, hypothalamus, medial thalamic nucleus, and raphe area (Arai et al, 1984;Tejani et al, 1993). Evidence has accumulated suggesting that noradrenaline is also involved in controlling body temperature (Lin et al, 1981, Sallinen et al, 1997, endocrine secretion (Endroczi et al, 1978;Valet et al, 1989;Ruffolo et al, 1991), and sexual behaviour (Morales et al, 1987;Guiliano & Rampin, 1997).…”
Section: Noradrenaline Functionsmentioning
confidence: 99%